Depresi, kecemasan, stress dan beban perawatan pengasuh utama (caregiver) pasien dengan stroke - Desi Risnarita; Teguh Pribadi; Prima Dian Furqoni; Rahma Elliya (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: A caregiver is someone who provides assistance to people who are disabled and need help due to illness or limitations such as spouses, children, in-laws, grandchildren, relatives, neighbors, friends, or other kinship relationships. Caregivers have the task of assisting in mobility, communication, self-care, and emotional and psychological changes so caregivers must balance the dual responsibility role of caring for stroke patients and adjusting their lifestyle. The weaker and more chronic the patient's illness, the higher the burden experienced by the caregiver.Purpose: To determine the relationship variables depression, anxiety, and stress with the burden of care among caregivers of patients with stroke.Method: Quantitative, analytic cross-sectional design. The population in this study were caregivers with 80 respondents, the sampling technique used was accidental sampling. Analysis using chi-square testResults: On average, respondents experienced the most dominant mild depression 45 (56.25%), mild anxiety 35 (43.75%), stress 35 (43.75%), the burden of care for the main caregiver was mild-moderate 38 (47.5%)Conclusion: There is a relationship between the burden of primary caregiver care (caregiver) in stroke patients with depression (p-value 0.03), anxiety (p-value 0.02), and stress (p-value 0.04).Keywords: Depression; Anxiety; Stress; Burden of Primary; Caregiver; Patients; Stroke.Pendahuluan: Caregiver adalah seseorang yang memberikan bantuan pada orang yang mengalami ketidakmampuan dan memerlukan bantuan karena penyakit atau keterbatasannya seperti pasangan, anak, menantu, cucu, saudara, tetangga, teman maupun hubungan kekerabatan lainnya. Caregiver memiliki tugas membantu dalam mobilitas, komunikasi, perawatan diri, perubahan emosional dan psikologis sehingga caregiver harus menyeimbangkan peran tanggung jawab ganda merawat pasien stroke serta menyesuaikan gaya hidupnya. Semakin lemah dan kronis penyakit pasien maka semakin tinggi beban yang dialami caregiver.Tujuan: Diketahui hubungan depresi, kecemasan, stress dengan beban perawatan pengasuh utama pada pasien stroke.Metode: Penelitian kuantitatif, desain analitik rancangan cross sectional. Populasinya caregiver/pengasuh pasien stroke dan besar sampel yang diambil sebanyak 80 responden. Teknik pengambilan sampel menggunakan accidental sampling. Analisis menggunakan uji chi square.Hasil: Rata-rata responden mengalami yang paling dominan depresi ringan 45 (56.25%), kecemasan ringan 35 (43.75%), stress 35 (43.75%), beban perawatan pengasuh utama beban ringan-sedang 38 (47.5%).Simpulan: Ada hubungan antara beban perawatan pengasuh utama (caregiver) pada pasien stroke dengan depresi (p-value 0.03), kecemasan (p-value 0.02), stress (p-value 0.04).